Parámetros hematológicos del búfalo de agua ( Bubalus bubalis ) en Ecuador. - Jiménez González, Marco Xavier (2021)
In order to characterize the hematological and biochemical profiles of the water buffalo (Bubalus bubalis), this research was carried out in order to contribute and publicize the health reality in which the species has been developing in Ecuador and its regions of study interest, littoral or coast, inter-Andean or sierra and eastern or Amazon. The study was developed in 84 animals in a completely randomized design (DCA) factorial (3x2x2) and an analysis of variance (p <0.05), highlighting three regions of interest already specified, two ages between 1 - 3 years and 3 - 5 years respectively and divided between the two sexes. The following general values detailed below were obtained and taking into account the (Mean ± SE) for the biochemical profile with its variables, GLU mg / dL 55.36 ± 1.95, CREA mg / dL 1.57 ± 0.05 , BUN mg / dL 11.94 ± 0.41, BUN / CREA ratio 8.42 ± 0.4, TP mg / dL 8.18 ± 0.17, ALB mg / dL 3.17 ± 0.05, GLOB mg / dL 4.95 ± 0.14, ALB / GLOB ratio 0.66 ± 0.02, ALT U / L 91.76 ± 3.3, ALKP U / L 180.8 ± 15.29 with their general values for the biometric profile in its (Mean ± SE) with its variables% HCT 35.92 ± 0.7, HGB (g / dL) 12.25 ± 0.26, MCHC (g / dL) 34.3 ± 0, 18, # LEU K / μL 7.49 ± 0.43, # GRANS K / μL 2.55 ± 0.18,% GRANS 34.53 ± 1.38, L / M x10ᶺ9 / L 5.16 ± 0, 36,% L / M 65.86 ± 1.42, PLAQ K / μL 180.8 ± 15.29 respectively. Hoping that the data obtained in this trial will be of practical use when making an adequate clinical assessment of the animals and also serve as a contribution to the development of the sanitary management of the species in the country.